Pengaruh Service Quality dan Social Media Marketing pada Customer Engagement dan Purchase Intention - Esti Natasya Sitanggang (As-Syirkah: Islamic Economic & Financial Journal, 2025)
This study aims to analyze the effects of Service Quality and Social Media Marketing on Customer Engagement and purchase intention among K-pop fans in Jakarta who have never purchased K-pop merchandise. This study employs a quantitative approach with a non-probability sampling method, specifically purposive sampling, involving 155 samples collected by distributing questionnaires via Google Forms. Furthermore, respondents' responses were analyzed using Structural Equation Model (SEM) analysis on Partial Least Square . The results showed that service quality and social media marketing have a positive effect on customer engagement. Customer engagement has a positive effect on purchase intention. However, service quality does not have a significant impact on purchase intention because good and consistent online service does not necessarily increase fans' desire to buy products. Finally, social media marketing also has a direct positive influence on purchase intention. The managerial implications underscore the importance of a social media marketing strategy that is engaging, interactive, and fan-friendly in driving engagement and purchase intent. Good technical service needs to be complemented with an emotional approach to be more effective. Visual content such as product teasers, product unboxing videos, or idol posts can strengthen fan engagement. Regular evaluation of content performance and building consistent emotional connections are key to increasing purchase intention amid ever-changing popular culture.